Mass Spectrometric Analysis of TRPM6 and TRPM7 Phosphorylation Reveals Regulatory Mechanisms of the Channel-Kinases - Cai, Na (Sci Rep, 2017)
TRPM7 and TRPM6 were the first identified bifunctional channels to contain their own kinase domains, but how these channel-kinases are regulated is poorly understood. Previous studies identified numerous phosphorylation sites on TRPM7, but very little is known about TRPM6 phosphorylation or sites on TRPM7 transphosphorylated by TRPM6. Our mass spectrometric analysis of homomeric and heteromeric TRPM7 and TRPM6 channels identified phosphorylation sites on both proteins, as well as several prominent sites on TRPM7 that are commonly modified through autophosphorylation and transphosphorylation by TRPM6. We conducted a series of amino acid substitution analyses and identified S1777, in TRPM7’s catalytic domain, and S1565, in TRPM7’s exchange domain that mediates kinase dimerization, as potential regulatory sites. The phosphomimetic S1777D substitution disrupted catalytic activity, most likely by causing an electrostatic perturbation at the active site. The S1565D phosphomimetic substitution also inactivated the kinase but did so without interfering with kinase dimerization. Molecular modeling indicates that phosphorylation of S1565 is predicted to structurally affect TRPM7’s functionally conserved N/D loop, which is thought to influence the access of substrate to the active site pocket. We propose that phosphorylation of S1565 within the exchange domain functions as a regulatory switch to control TRPM7 catalytic activity.